Community-Inquiry: Current Perspectives on Freshmen’s Verbal and Written Feedback from Sophomores Students of EFL Writing - Hanifiyah, Lina; Ivone, Francisca Maria; Rachmajanti, Sri (Journal of Languages and Language Teaching, 2024)
A community of inquiry can help students increase engagement that supports English language acquisition. The community- inquiry provides students not only with cognitive but also social intelligence. Therefore, this study aimed to explore the perceptions of sophomores' verbal and written feedbacks on freshmen’s writing. This small-scale study examined 25 students attending an Intensive English Course in the English Literature Department at Universitas Islam Negeri Maulana Malik Ibrahim Malang. It involved sophomores providing verbal and written feedbacks on freshmen's writing, reflecting the implementation of a community of inquiry. The study employed a case study method, using three types of questionnaires to gather students' opinions on sophomores' written feedbacks, their perceptions of the verbal feedbacks, and their descriptive writing competence following the feedback process. The study revealed that both the sophomores' verbal and written feedbacks were beneficial for improving the freshmen's writing skills. Furthermore, the process of receiving feedbacks also appeared to enhance the students' confidence in their writing.Verbal and written feedback from the sophomores not only clarifies the aspects for the improvement of the composition but also improves the freshmen’s self-confidence to write better. The feedbacks are effective since the students are of the same age, the freshmen can relate better, and the feedback they receive matches their style. However, this type of mentorship also has drawbacks because the sophomores’ knowledge is limited, so the input they can provide is also limited.  Therefore, it is suggested that English lecturers take advantage of sophomores' verbal and written feedbacks to assist freshmen in developing their writing skills.